Increased both PD–L1 and PD–L2 expressions on monocytes of patients with hepatocellular carcinoma was associated with a poor prognosis - Yasuoka, Hidetaka (Sci Rep, 2020)
Anti-programmed cell death-1 (PD-1) antibodies has been approved to treat HCC. Some PD-1 ligands (PD–L1 and PD–L2) negative tumors respond to treatment of anti-PD-1 antibodies, and this fact may be caused by the expression of PD-1 ligands on non-tumor cells. PD–L1 was recently found to be expressed on CD14(+) cells from cancer patients. We investigate PD-1 ligands expression on CD14(+) cells of patients with HCC and the role of CD14(+) cells in an antitumor response. In this study, 87 patients diagnosed with HCC were enrolled. CD14(+) cells from patients with HCC expressed PD–L1 (4.5–95.5%) and PD–L2 (0.2–95.0%). According to cut-off values, we classified patients as those either with PD–L1(+)PD–L2(+)CD14(+) cells or other types of CD14(+) cells. The overall survival of patients with PD–L1(+)PD–L2(+)CD14(+) cells was shorter than that of patients with other types of CD14(+) cells (p = 0.0023). PD–L1(+)PD–L2(+)CD14(+) cells produced IL-10 and CCL1, and showed little tumoricidal activity against HepG2 cells. The tumoricidal activity of CD8(+) cells from patients with PD–L1(+)PD–L2(+)CD14(+) cells were suppressed by co-cultivation with CD14(+) cells from the syngeneic patient. Furthermore, anti-PD-1 antibody restored their tumoricidal activity of CD8(+) cells. In conclusion, some patients with HCC have PD–L1(+)PD–L2(+)CD14(+) cells that suppress their antitumor response. These inhibitory functions of CD14(+) cells may be associated with a poor prognosis in these patients.